PERICYTES AS TARGETS IN HEREDITARY HEMORRHAGIC TELANGIECTASIA - Thalgott, Jérémy; Dos-Santos-Luis, Damien; Lebrin, Franck (Frontiers in Genetics, 2015)
Defective paracrine Transforming Growth Factor-β TGF-β) signaling between endothelial cells and the neighboring mural cells have been thought to lead to the development of vascular lesions that are characteristic of Hereditary Hemorrhagic Telangiectasia (HHT). This review highlights recent progress in our understanding of TGF-β signaling in mural cell recruitment and vessel stabilization and how perturbed TGF-β signaling might contribute to defective endothelial-mural cell interaction affecting vessel functionalities. Our recent findings have provided exciting insights into the role of thalidomide, a drug that reduces both the frequency and the duration of epistaxis in individuals with HHT by targeting mural cells. These advances provide opportunities for the development of new therapies for vascular malformations.